Clinical Efficacy of Modified Small Incision Thyroidectomy and Analysis of Influencing Factors of Postoperative Hypocalcemia - Zhou, Jian; Ju, Hongqing; Ma, Hongyan; Diao, Qixian (Frontiers in Surgery, 2022)
Objective: to analyze the clinical effect of modified small incision thyroidectomy and evaluate the influencing factors of hypocalcemia (EH) in patients after operation. Methods: A total of 220 cases of thyroid cancer were selected from October 2019 to October 2021 in our hospital. The patients were divided into a control group and an observation group by random number method, 110 cases in each group. Patients in the control group were treated with traditional thyroidectomy, while patients in the observation group were treated with modified small incision surgery. The perioperative indexes of the two groups were compared. The thyroid hormone indexes of the two groups were detected before operation and 7 days after operation, and the incidence of complications in the two groups was compared. Blood calcium of patients in the two groups was detected 7 days after surgery. According to the blood calcium level of patients, they were divided into EH group and normal group. The data of two groups were compared and the related factors affecting the occurrence of EH after operation were analyzed. Results: The operation time, incision length and intraoperative bleeding volume of patients in the observation group were significantly lower than those of patients in the control group (P<0.05). There was no significant difference in drainage time and postoperative drainage volume between the two groups (P>0.05). The postoperative PTH level of patients in the observation group was significantly higher than that in the control group (P<0.05), but there was no significant difference in FT3, FT4 and TSH levels (P>0.05). The incidence of postoperative complications in the observation group (11.82%) was significantly lower than that in the control group (34.55%). Conclusion: The modified small incision technique can effectively reduce the blood loss, operation time, incision length and other operation related indicators in patients with thyroid cancer, and reduce the surgical trauma and related complications. Bilateral lymph node dissection, parathyroidectomy and PTH decline are the risk factors for EH in patients with thyroid cancer after surgery. Comprehensive imaging examination should be conducted for patients during the perioperative period.